Serpulidae (Annelida) of Lizard Island, Great Barrier Reef, Australia - Kupriyanova, Elena; Sun, Yanan; ten Hove, Harry A.; Wong, Eunice; Rouse, Greg W. (Zootaxa, 2015)
Serpulidae are obligatory sedentary polychaetes inhabiting calcareous tubes that are most common in subtropical and tropical areas of the world. This paper describes serpulid polychaetes collected from Lizard Island, Great Barrier Reef, Australia in 1983–2013 and deposited in Australian museums and overseas. In total, 17 serpulid genera were recorded, but although the study deals with 44 nominal taxa, the exact number of species remains unclear because a number of genera (i.e., Salmacina, Protula, Serpula, Spirobranchus, and Vermiliopsis) need world-wide revisions. Some species described herein are commonly found in the waters around Lizard Island, but had not previously been formally reported. A new species of Hydroides (H. lirs) and two new species of Semivermilia (S. annehoggettae and S. lylevaili) are described. A taxonomic key to all taxa found at Lizard Island is provided.
World Polychaeta Database (WPolyDb). Open access at Zootaxa